Antibacterial Mechanism of N‐PMI and the Characteristics of PMMA‐Co‐N‐PMI Copolymer. Issue 6 (17th May 2022) - Shi, Han; Zhuang, Qixin; Zheng, Anna; Zhan, Pengfei; Guan, Yong; Wei, Dafu; Xu, Xiang; Wu, Tao
Abstract: Aiming at the excellent killing effect of N‐phenylmaleimide (N‐PMI) on microorganisms, this article used structural simulation analysis, fluorescence analysis, confocal laser scanning microscope and SEM to find that the double bond in N‐PMI could interact with the sulfur groups in the membrane protein, changing its conformation, rupturing the plasma membrane of the cell, leaking the contents, and ultimately causing the death of the microorganisms. Therefore, once the double bond participated in the polymerization, N‐PMI lost its antimicrobial function. N‐PMI could achieve azeotropic copolymerization with MMA through reactive extrusion polymerization. N‐PMI with a content of 5 % can be evenly inserted into the PMMA chain segment during the copolymerization reaction, thereby increasing the Tg of pure PMMA by up to 15 °C, which provided the PMMA‐co‐PMI copolymer with resistance to boiling water sterilization advantageous conditions. In addition, N‐PMI with a content of 5 % has little effect on the transparency of PMMA after participating in the copolymerization. Moreover, the trace amount of residual N‐PMI made the material have excellent antimicrobial function, and the bacteriostatic zone is extremely small, which provided an excellent guarantee for the safety and durability of the material. As a medical biological material, the PMMA‐co‐PMI copolymer has a good industrialization application prospects. Abstract :